New mean charts for bivariate asymmetric distributions using different ranked set sampling designs. Issue 5 (3rd September 2018) - Koyuncu, N.; Karagöz, D.
ABSTRACT: The purpose of this study is to construct the mean control chart limits based on Shewhart, weighted variance and skewness correction methods using simple random sampling, ranked set sampling, median ranked set sampling and neoteric ranked set sampling designs. Type I Marshall-Olkin bivariate Weibull and bivariate lognormal distributions are used in the proposed mean control charts. The performance of the proposed control charts based on neoteric ranked set sampling designs is compared with their counterparts in ranked set sampling, median ranked set sampling and simple random sampling by Monte Carlo simulation. Simulation results revealed that the proposed mean charts perform much better than simple random sampling design.